2015
DOI: 10.1111/ics.12290
|View full text |Cite
|
Sign up to set email alerts
|

MRI as a promising tool for evaluation of the stability of cosmetic emulsions

Abstract: MRI is a promising tool for evaluation of the stability of cosmetic emulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Histogram analysis allows us to discuss the emulsion state quantitatively. 10,11) The mean values were 20.13±0.51, 23.47±0.44, and 18.60±0.26 ms, respectively for FLU, FUR, and the moisturizing cream. The values for FLU and FUR were distinct from those of the moisturizing cream, indicating that T 2 mapping makes it possible to distinguish each pharmaceutical in the admixture as long as they are unmixed.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Histogram analysis allows us to discuss the emulsion state quantitatively. 10,11) The mean values were 20.13±0.51, 23.47±0.44, and 18.60±0.26 ms, respectively for FLU, FUR, and the moisturizing cream. The values for FLU and FUR were distinct from those of the moisturizing cream, indicating that T 2 mapping makes it possible to distinguish each pharmaceutical in the admixture as long as they are unmixed.…”
Section: Resultsmentioning
confidence: 94%
“…During the accelerated testing, their emulsion states were monitored by T 2 mapping. 9,10) From these studies, T 2 mapping proved to be effective for detecting the change in emulsion state (e.g., creaming and phase separation).…”
mentioning
confidence: 99%
“…We have already found that T 2 mapping is a powerful tool with which to evaluate the stability of emulsions. [8][9]12) The acquired T 2 maps clearly display the phase separation with distinct T 2 values (Figs. 5a, c).…”
Section: Resultsmentioning
confidence: 97%
“…From our previous studies, it has been confirmed that T 2 maps are a powerful tool to detect phase separation in pharmaceutical emulsions. 10,11,15) As far as oil-in-water (o/w)-type emulsion is concerned, the state of water is substantially changed depending on its surroundings.…”
Section: Effects Of Surfactants On the Emulsion Stability Of The Creammentioning
confidence: 99%
“…It is worth noting that the detection sensitivity of change in the emulsion state is much superior to that by visible observation. 12,15) The creams containing various surfactants were stored at 40°C, and their phase separations were monitored continuously. As shown in Fig.…”
Section: Effects Of Surfactants On the Emulsion Stability Of The Creammentioning
confidence: 99%